Over-splitting destabilizes the taxonomy of hylaranine frogs: A response to Chandramouli et al. (2020) - Chan, Kin Onn; Abraham, Robin K.; Sanguila, Marites B.; Brown, Rafe M. (Zootaxa, 2020)
In a recent article, Chandramouli et al. (2020) re-assessed the systematic position of the hylaranine frog Indosylvirana nicobariensis and proposed a new monotypic genus, Bijurana, for this species. The authors re-examined the type series of specimens and attempted to justify the recognition of a new genus using morphological and phylogenetic data. They concluded that the taxon’s unique phylogenetic position, high genetic divergence (uncorrected p-distance ≥ 13.64% of the 16S rRNA mitochondrial gene), and a unique combination of morphological characters warranted the erection of the new genus.